Chemical Engineering and Technology in Mineral Processing and Extractive Metallurgy - Wang, Shuai; Wang, Xingjie; Yang, Jia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Chemical engineering and technology are the basis of mineral processing and extractive metallurgy. In the long history of human civilization, with the development of science and technology, chemical engineering, mineral processing, metallurgical engineering, and other process technologies have coexisted and mutually benefited each other. More than 100 years ago, chemical engineers summarized the common laws in the process industry and built up the basic theory of unit operations. It is undoubtedly of great significance to study the chemical engineering principles in mineral processing and extractive metallurgy to profoundly understand the essence of mineral separation and extraction, optimizing the technological flow of mineral processing and improving the utilization level of mineral resources. The purpose of this book is to discuss chemical engineering principles in mineral processing and extractive metallurgy to improve the utilization of mineral resources. Experts, technicians, and students in the fields of chemical engineering, metallurgy, and mineral processing are welcome to read this book.